UJI AKTIVITAS ANTIMIKROBA SERTA ANTIOKSIDAN ASAP CAIR CANGKANG SAWIT (Elaeis gueneensis jack) - Yefrida -; Refilda -; Indrawati -; Irma Yanti Siregar (Universitas Andalas, 2011)
ABSTRACT Liquid smoke is one of natural preservative. It can make from many sources such as coconut shell, wood, etc. In this study, it is made from the palm kernel shell (Elaeis gueneensis jack) by using pirolysis method. Its contains is determined by GC-MS, while antimicrobial activity by Kirby-Bauer method and antioxidant activity by DPPH method. From the test, it can be concluded that this liquid smoke contains carboxylic acids, fenol and its derivative compound as a major component and has a good enough antimicrobial and antioxydant activity. Keywords : liquid smoke, pirolysis, antimicrobial, antioxvdant.